Factors affecting Thai EFL students’ behavioral intentions toward mobile-assisted language learning - Pan, Li; Ye, Yan; Li, Xinyi (Frontiers in Education, 2024)
Recently, researchers have begun to pay more attention to topics related to the adoption of mobile devices for supporting second or foreign language learning. Mobile-assisted language learning (MALL) is now prevalent among language learners and educators because of its convenient and enjoyable features. This study combined and extended the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT) to investigate the factors influencing English as a Foreign Language (EFL) students' behavioral intentions to use MALL at two universities in Bangkok, Thailand. A total of 507 valid responses were obtained by using three-step sampling. After using confirmatory factor analysis (CFA) to determine that the study had enough construct validity, structural equation modeling (SEM) was applied to test the research's hypotheses. The findings revealed that all 15 hypotheses were supported, except that social influence cannot significantly influence behavioral intention. By acquiring a deeper understanding of the factors that impact the behavioral intentions of language learners to utilize MALL, developers and providers can improve their capacity to design more enjoyable and effective applications that align with customer expectations and enhance financial gains. By understanding students' behavioral intentions towards MALL, educators can efficiently raise awareness of its benefits and provide effective training, enabling students to utilize available resources and enhance their language learning experience.